To solve the equation −4(z + 12) = 36 for z, we can begin by distributing the −4 through the parentheses:
−4z − 48 = 36
Next, we can isolate the variable z by adding 48 to both sides of the equation:
−4z = 36 + 48
−4z = 84
Finally, we can solve for z by dividing both sides of the equation by −4:
z = 84 / −4
Simplifying the division gives:
z = -21
Therefore, the solution to the equation is z = -21.
What is the solution of the equation −4(z + 12) = 36 when solving for z
? (1 point)
Responses
−6
negative 6
−21
negative 21
21
21
24
1 answer